A titration model for evaluating calcium hydroxide removal techniques - Mark PHILLIPS; Scott McCLANAHAN; Walter BOWLES (University of São Paulo, 2015)
Objective Calcium hydroxide (Ca(OH)2) has been used in endodontics as an intracanal medicament due to its antimicrobial effects and its ability to inactivate bacterial endotoxin. The inability to totally remove this intracanal medicament from the root canal system, however, may interfere with the setting of eugenol-based sealers or inhibit bonding of resin to dentin, thus presenting clinical challenges with endodontic treatment. This study used a chemical titration method to measure residual Ca(OH)2 left after different endodontic irrigation methods. Material and Methods Eighty-six human canine roots were prepared for obturation. Thirty teeth were filled with known but different amounts of Ca(OH)2 for 7 days, which were dissolved out and titrated to quantitate the residual Ca(OH)2 recovered from each root to produce a standard curve. Forty-eight of the remaining teeth were filled with equal amounts of Ca(OH)2 followed by gross Ca(OH)2 removal using hand files and randomized treatment of either: 1) Syringe irrigation; 2) Syringe irrigation with use of an apical file; 3) Syringe irrigation with added 30 s of passive ultrasonic irrigation (PUI), or 4) Syringe irrigation with apical file and PUI (n=12/group). Residual Ca(OH)2 was dissolved with glycerin and titrated to measure residual Ca(OH)2 left in the root. Results No method completely removed all residual Ca(OH)2. The addition of 30 s PUI with or without apical file use removed Ca(OH)2 significantly better than irrigation alone. Conclusions This technique allowed quantification of residual Ca(OH)2. The use of PUI (with or without apical file) resulted in significantly lower Ca(OH)2 residue compared to irrigation alone.